(untitled) (Eurasian Research Bulletin, 2023)
The article lists the varietal branching ratio and branch elongation indicators for microclonal branching of cherry varieties under the influence of MS, DKW, and MSTAK in nutrient media under in vitro conditions BAP-0.30, 1.0 mg/l, TDZ – 0.50, 1.0, and MetP - 0.20, 0.30, 0.50, and 1.0 mg/L.